Characterization And Utilization Of Extracted Starch And Particles From Oil Palm Trunk For Particleboard Manufacturing - Mohd Salleh, Kushairi (2014)
This study investigated the potential of the oil palm particles and oil palm starch produced and extracted from the oil palm trunk. Commercial rubberwood particles and wheat starch were used as a comparison. The starches were modified with polyvinyl alcohol to change its properties for better performance. Basic properties of raw materials were determined for their final properties of the boards. The raw materials were also characterized using scanning electron microscopy, xray diffractometry analysis, thermogravimetric analysis, and differential scanning calorimetry analysis. Comparisons were made between boards and panels bonded with urea formaldehyde were used as a control board. The physical and mechanical testing carried out based on japanese industrial standard a5908, which include density, moisture content, dimensional stability testing, and mechanical strength. All mechanical properties met the requirements, but none of the physical properties met the requirements except for moisture content. The panels made using the oil palm particles and bonded with the oil palm starch showed better mechanical properties, but poor dimensional stability compared to those panels made with the rubberwood particles, and panels bonded with the wheat starch.